Analysis of factors affecting the evolution of the sign system and the duality of identity in the urban context with a semiotic approach - azadeh atashpanjeh; mohammad naghizadeh; Zahrasadat saeideh zarabadi (تحقیقات کاربردی علوم جغرافیایی, 2021)
In today's urban planning, the paraphrastic processes of symbolic systems in the city, which aim to show the social and cultural meaning of the physical environment, have received less attention, and most urban contexts, regardless of significant and identifiable differences and similarities and the hidden values in the context and the patterns of traditional urban planning and architecture of Iran are formed, and this makes it important to analyze these processes. The object of this paper is to present a framework for considering change of semiotics system caused by factors affecting the urban identity and comparing these systems in the old and new textures of the city by layered attitude toward the city as a multimedia text. The research is qualitative and the method of research is descriptive-analytic analytic and Semiotics has been used as a tool and method for considering representations and analyzing the identity of the city. Studies in the old context relied heavily on documents and in the new context is field and the samples were studied in hot and dry areas of Iran.The results show that based on the study of representations in the symbolic system in the textual layers of the city form, the duality of meaning and identity of the old and new textures of a city over time indicate several main factors of change within the textual layers of the form of city, the rupture and duality in the human layer and change in the system of codes that affect the structure of the city form, which is manifested in the elimination, replacement or change of signs in the natural, social and artificial layers.